2022
DOI: 10.1136/bmjopen-2021-057418
|View full text |Cite
|
Sign up to set email alerts
|

Usual source of primary care and preventive care measures in the COVID-19 pandemic: a nationwide cross-sectional study in Japan

Abstract: ObjectivesTo assess multiple preventive care measures and to examine their associations with having a usual source of primary care and primary care performance during the COVID-19 pandemic in Japan.DesignNationwide cross-sectional study.SettingJapanese general adult population.Participants1757 adult residents.Primary outcome measuresFourteen preventive care measures aggregated the overall screening, immunisation and counselling composites.ResultsDepression screening, zoster vaccination and tetanus vaccination … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…In a Norwegian study [ 18 ], compared with the same period in 2019, the number of individuals seeking inpatient services for mental health declined from 16 to 7. Asian countries such as South Korea, Japan, and Australia, and the United States also found that the utilization of mental health services declined during the COVID-19 period [ 19 , 20 , 21 , 22 ]. This phenomenon may be the result of strict isolation measures and medical restrictions, which delayed patient admission plans.…”
Section: Discussionmentioning
confidence: 99%
“…In a Norwegian study [ 18 ], compared with the same period in 2019, the number of individuals seeking inpatient services for mental health declined from 16 to 7. Asian countries such as South Korea, Japan, and Australia, and the United States also found that the utilization of mental health services declined during the COVID-19 period [ 19 , 20 , 21 , 22 ]. This phenomenon may be the result of strict isolation measures and medical restrictions, which delayed patient admission plans.…”
Section: Discussionmentioning
confidence: 99%
“…The data for this study were sourced from the National Usual source of Care Survey (NUCS), which was conducted in May 2021 during the COVID-19 fourth wave in Japan. The NUCS was a nationwide mail survey that collected data on the USC, patient experience of primary care, healthcare utilisation, health conditions, health-related quality of life and sociodemographic characteristics of a representative sample of the Japanese adult population 7. One of the primary research objectives of the NUCS was to evaluate primary care access for COVID-19 consultation among residents who have a USC and to examine their associations with patient experience.…”
Section: Methodsmentioning
confidence: 99%
“…The NUCS was a nationwide mail survey that collected data on the USC, patient experience of primary care, healthcare utilisation, health conditions, health-related quality of life and sociodemographic characteristics of a representative sample of the Japanese adult population. 7 One of the primary research objectives of the NUCS was to evaluate primary care access for COVID-19 consultation among residents who have a USC and to examine their associations with patient experience. In the NUCS, a nationally representative panel in Japan, which was administered by the Nippon Research Center, was used to select potential participants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations